Một vài khía cạnh lý thuyết của các thuật toán dò biên - Ky, Nguyen Ngoc (Journal of Computer Science and Cybernetics, 2018)
One of most important stages of image processing is bound following – In this paper we present a new criterion of correctness of one bound following algorithm, the necessary and sufficient condition of correctness is found. Some bound following operators have been considered and verified.